Banking Sector Integration and Competition in CEMAC - Vacher, Jerome; Saab, Samer (Washington, D.C. : International Monetary Fund, 2007)
This paper considers the extent of retail banking integration in the Communaute Economique et Monetaire d'Afrique Centrale (CEMAC) and the level of bank competition at the regional level. Using a mix of quantitative and qualitative indicators, the paper finds some evidence of price convergence in average interest rate spreads. However, this observed fact is not supported by an increase in cross-border flows in retail loans and deposits, and price convergence may merely reflect excess liquidity in the region. Other data also indicate that bank competition within the CEMAC as a region is limited, complementing the findings on integration. Addressing shortfalls in legal and regulatory frameworks, infrastructure, and markets would facilitate integration.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Cameroon